2007
DOI: 10.1038/sj.onc.1210894
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib and a novel COX-2 inhibitor ON09310 upregulate death receptor 5 expression via GADD153/CHOP

Abstract: Cyclooxygenase-2 (COX-2) inhibitors are promising anticancer agents but their long-term use at high doses is associated with adverse cardiovascular events. The molecular mechanisms underlying the anticancer or toxic cardiovascular effects of COX-2 inhibitors remain unknown. Here we report that COX-2-selective celecoxib and a novel COX-2 inhibitor ON09310 upregulate death receptor 5 (DR5) and cooperate with tumor necrosis factor-related apoptosisinducing ligand (TRAIL), the ligand for DR5, to induce apoptosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 13 publications
2
19
3
Order By: Relevance
“…Previous studies have reported that celecoxib induced apoptosis via upregulation of DR5 in several cancer cells (22,23). However, in this study, celecoxib alone did not induce apoptosis ( Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous studies have reported that celecoxib induced apoptosis via upregulation of DR5 in several cancer cells (22,23). However, in this study, celecoxib alone did not induce apoptosis ( Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…In line with earlier studies (37-39) we find increased TRAIL-R2 surface expression on bortezomib treatment. TRAIL receptor expression can be transcriptionally upregulated by the endoplasmic reticulum-stress related protein CHOP (40), by NFkB (41) and p53 (42). However, we do not detect any changes in the total amount of TRAIL-R2 protein in whole cell lysates, indicating that bortezomib may trigger increased TRAIL-R2 surface expression without detectable changes in total protein expression of TRAIL-R2 in glioblastoma cells.…”
Section: Discussioncontrasting
confidence: 45%
“…In addition, tumor metastases and invasion occur when the TRAIL-induced apoptosis pathway is impeded (11,16,37). Recent studies suggested that inhibition of COX-2 increased the sensitivity of hepatocellular carcinoma cells to TRAIL (17,38,39). In this study, our data showed that Ad-TM showed dramatic hepatocellular carcinoma cytotoxicity via COX-2 gene silencing coupled with TRAIL expression in both in vitro and in vivo conditions.…”
Section: Discussionsupporting
confidence: 53%